Introduction to Thematic Issue: Collaborative Innovation in African Settings - (:unkn) unknown (My University, 2020)
An introduction to the articles in this AJIC Thematic Issue: Collaborative Innovation in African Settings, which features findings from research conducted by members of the Open African Innovation Research (Open AIR) network.